Intervertebral Disc Regeneration (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book provides a brief snapshot of recent research on the subject of intervertebral disc degeneration and how this specific organ could be regenerated. It provides stimuli to the reader in representing research from different angles in this cross-disciplinary field of spine surgeons, mechanical engineers and biologists. In particular, it is instructive as to how disc herniations could be successfully induced in vitro and, also, to how novel cell-based therapies using rare autochthonous stem cells could potentially be used in the future.